Copper-catalyzed intermolecular Regio- and Enantioselective Hydrosilylation of Alkenes with Prochiral Silanes - Xiao-Yan Zhu; Wenyu Gao; Jian-Lin Xu; Zi-Lu Wang; Jin-Bo Zhao; Yun-He Xu (Nature Communications)
Abstract This study presents a copper-catalyzed, substrate-controlled regio- and enantioselective intermolecular hydrosilylation method capable of accommodating a broad scope of alkenes and prochiral silanes. The approach offers an efficient and versatile pathway to generate enantioenriched linear and branched alkyl-substituted Si-stereogenic silanes. Key features of this reaction include mild reaction conditions, simple catalytic systems, compatibility with diverse substrates, high yields and enantioselectivities.